Circuitry of power supplies for pulsed arc welding with chaotic current oscillations - V. N. Sidorets; A. I. Bushma; A. M. Zhernosekov (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The phenomenon of deterministic chaos in nonlinear systems is of interest to researchers firstly for its fundamental aspects. Recently, the tendency has changed from fundamental to applied research. Deterministic chaos was found in electrical circuits with a welding arc and its fundamental properties were investigated. The technological advantages of pulsed oscillations in circuits with laser-arc discharge over welding processes were shown earlier. The authors have reason to believe that the application of chaotic oscillations also has a positive effect. Only experimental studies can confirm this assumption. The purpose of this work is to develop promising circuit solutions for specialized power supply with current chaotic oscillations. Application of set-top boxes to the existing power sources to create chaotic oscillations of pulsed current arc has been proposed. The development of circuit design has been based on the results of previous studies of deterministic chaos in RLC-circuits with electric arc. The advantages and disadvantages of various circuits have been discussed in order to select schemes of set-top boxes for the practical implementation.